2003
DOI: 10.1152/ajpheart.00128.2003
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic effect of albumin and fibrinogen on immunoglobulin-induced red blood cell aggregation

Abstract: Therapeutic administration of immunoglobulins (Ig) has the potential to precipitate thrombotic events. This phenomenon may be explained by red blood cell (RBC) aggregation, which can be potentiated by Ig. The contribution of plasma albumin and fibrinogen to Ig-induced RBC aggregation is unclear. We examined RBC aggregation in three settings: 1) patients receiving therapeutic infusions of Ig; 2) patients receiving plasma supplemented in vitro with Ig; and 3) patients receiving RBC suspensions in standard buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 34 publications
4
77
0
Order By: Relevance
“…Specifically, obesity is accompanied by increased circulating CRP and fibrinogen concentrations. 4,17,18,30 The latter is a well-characterized RBC aggregation inducer, [31][32][33][34][35][36] either through a nonspecific mechanism 31,32 or by specific binding of fibrinogen to RBC surface membranes, 36 and thus bridging between the cells. Furthermore, CRP has been shown to correlate with indexes of RBC aggregation as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, obesity is accompanied by increased circulating CRP and fibrinogen concentrations. 4,17,18,30 The latter is a well-characterized RBC aggregation inducer, [31][32][33][34][35][36] either through a nonspecific mechanism 31,32 or by specific binding of fibrinogen to RBC surface membranes, 36 and thus bridging between the cells. Furthermore, CRP has been shown to correlate with indexes of RBC aggregation as well.…”
Section: Discussionmentioning
confidence: 99%
“…The complex interactions between these macromolecules, as well as albumin, in the formation of RBC aggregates were demonstrated recently in an in vitro model by our group. 35 Furthermore, altered glucose and lipoprotein concentrations are also typical to obesity; thus, we evaluated the contribution of LDL and glucose levels to the pathological formation of large and resistant RBC aggregates. We found that neither of these candidates were significant contributors to the phenomenon, as have been found previously.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Other methods used to study RBC aggregation are microscopy and image analyses, photoacoustics, and sedimentation. 4,14,15 However, these methods are not suitable for studying cell interaction mechanics, as they do not provide detailed information about individual cell-to-cell interactions. Methods such as micropipette aspiration, scanning electron microscopy (SEM), atomic force microscopy (AFM), and optical tweezers (OT) have been used to study RBC aggregation at the singlecell level and to assess the dynamics/mechanics of RBC interaction.…”
Section: Methods Used To Study Red Blood Cell Aggregationmentioning
confidence: 99%
“…In particular, there are results indicating both a decrease and elevation of the aggregation level after albumin is added to the solution. 14,29 Among blood plasma proteins (macromolecules) affecting RBC aggregation, the main role is attributed to fibrinogen. Schechner et al 30 showed that fibrinogen is the most significant determinant of RBC aggregation.…”
Section: Factors Affecting Red Blood Cell Aggregationmentioning
confidence: 99%
“…Glutaraldehyde reduced the adhesion by about 25 % whereas fibronectin increased the adhesion by 10 % (Kendall & Stainton, 2001). Ben-Ami, R., et al suggested a three-way interaction among fibrinogen, Ig, and albumin that synergistically induces erythrocytes aggregation in plasma (Ben-Ami et al, 2003). It was indicated that depletion interaction might play a significant role in erythrocyte adhesion via initiating close contacts and thus suggest the importance of depletion forces for RBC interactions and its relevance to a wide variety of in vitro and in vivo cell-cell and cell-surface interactions (Z. W. Zhang & Neu, 2009 Vol.…”
Section: Resultsmentioning
confidence: 99%